The new gold standard : rediscovering the power of gold to protect and grow wealth - Nathan, Paul.; ebrary, Inc. (Hoboken, N.J. : John Wiley & Sons, 2011)
"Paul Nathan, an expert on the gold standard, has written the definitive modern guide to returning to a gold standard that will work for global markets that are far different than those that existed in the 1970s when the U.S. moved off the gold standard. Written for beginning and professional readers, Nathan succinctly and clearly explains the nature of sound money, the causes and cures of inflation and deflation, the importance of fiscal responsibility within a sound monetary system, and the reasons for recessions and depressions. He then offers guidance on how we can lean toward a gold standard (that doesn't involve extremist positions of abolishing the Fed and the like) that will strengthen the dollar, reduce debt, and help stabilize the economy. Booms and busts can never be prevented but depressions and recessions can be avoided with a sustainable, stable monetary policy. Finally, Nathan presents strategies for investing in gold now and in the future. Readers will learn that the international run toward gold is not a fad but a world in monetary transition. Everyone needs to understand what this means for their investments and their spending and saving"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Gold standard -- United States; Gold -- United States; Investments -- United States; Monetary policy -- United States; Inflation (Finance) -- United States; Electronic books